Bewertungen - Erwartungen - Gebrauch: Sprachgebrauchsnormen zur inneren Mehrsprachigkeit an der Universität - Vergeiner, Philip C. (2021)
This study examines norms on variety choice using the example of the University of Salzburg. On the one hand, questionnaires and interviews are examined with quantitative and qualitative methods to detect normative evaluations and expectations. On the other hand, regularities in the actual language use are uncovered through a variable analysis of video recorded university lectures.